An investigation on leadership styles in different cultures - Mostafa Emami (Management Science Letters, 2013)
During the past few years, there have been tremendous efforts on leadership style and various aspects of different leadership style. Some firms can achieve effective business performance by developing strong organizational culture and effective leadership while many studies indicate that firms can achieve effective business performance by developing strong organizational culture and effective leadership. This paper reviews recent advances on leadership style and various aspects of organizational cultures completed during the past few years. The paper concentrates on recently published articles appeared in the world.